2020
DOI: 10.1002/adma.201907267
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework Nanoparticles Induce Pyroptosis in Cells Controlled by the Extracellular pH

Abstract: Ion homeostasis is essential for cellular survival, and elevated concentrations of specific ions are used to start distinct forms of programmed cell death. However, investigating the influence of certain ions on cells in a controlled way has been hampered due to the tight regulation of ion import by cells. Here, it is shown that lipid‐coated iron‐based metal–organic framework nanoparticles are able to deliver and release high amounts of iron ions into cells. While high concentrations of iron often trigger ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
113
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(118 citation statements)
references
References 47 publications
1
113
0
4
Order By: Relevance
“…This allows the precise tuning of host–guest interactions and ultra‐high porosity, both of which are central for the high loading and release of active molecules [28a, 36, 181] . Reticular chemistry allows not only to use reticular nanoparticles as transport vehicles, but enables their scaffolds to be turned into active components for cancer treatment, [182] by providing linkers as active components [180c] or with metal species that affect cell growth [183] . The MOF nanoparticles can also exhibit optical and catalytic properties at the targeted site in vivo to help treat cancer, by catalyzing the formation of reactive oxygen species for photodynamic treatment [184] …”
Section: Specific Applications Of Nano‐objectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows the precise tuning of host–guest interactions and ultra‐high porosity, both of which are central for the high loading and release of active molecules [28a, 36, 181] . Reticular chemistry allows not only to use reticular nanoparticles as transport vehicles, but enables their scaffolds to be turned into active components for cancer treatment, [182] by providing linkers as active components [180c] or with metal species that affect cell growth [183] . The MOF nanoparticles can also exhibit optical and catalytic properties at the targeted site in vivo to help treat cancer, by catalyzing the formation of reactive oxygen species for photodynamic treatment [184] …”
Section: Specific Applications Of Nano‐objectsmentioning
confidence: 99%
“…Straightforward functionalization of the external surface of reticular nanoparticles facilitates cell uptake and can be used to introduces targeted functional groups for cell uptake, or even be used to deliver drug molecules [31] . External functionalization of reticular nanoparticles also affects the stability in vivo and enables the breakdown and application of their function only upon uptake by the cell [183] …”
Section: Specific Applications Of Nano‐objectsmentioning
confidence: 99%
“…Dies ermöglicht die präzise Abstimmung der Wirt‐Gast‐Interaktion und ihrer ultrahohen Porosität, die beide zentral sind, um eine hohe Beladung und Freisetzung von aktiven Molekülen zu ermöglichen [28a, 36, 181] . Retikuläre Chemie erlaubt nicht nur die Verwendung von retikulären Nanopartikeln als Transportvehikel, sondern macht ihr Gerüst zu einer aktiven Komponente für die Krebsbehandlung, [182] indem sie Linker als aktive Komponenten [180c] oder Zellwachstum beeinflussende Metallspezies bereitstellt [183] . MOF‐Nanopartikel können auch am Zielort in vivo optische und katalytische Eigenschaften aufweisen, um bei der Behandlung von Krebs zu helfen, indem sie die Bildung reaktiver Sauerstoffspezies katalysieren, die eine photodynamische Behandlung von Krebs ermöglichen [184] …”
Section: Anwendungen Des Nanobereichsunclassified
“…Eine unkomplizierte Funktionalisierung der äußeren Oberfläche von retikulären Nanopartikeln erleichtert die Zellaufnahme und kann dazu verwendet werden, gezielt funktionelle Gruppen für die Zellaufnahme einzuführen, oder sogar zur Abgabe von Wirkstoffmolekülen verwendet werden [31] . Externe Funktionalisierung von retikulären Nanopartikeln beeinflusst ebenfalls die Stabilität in vivo und ermöglicht den Abbau sowie das Ausüben ihrer Funktion erst bei Aufnahme durch die Zelle [183] …”
Section: Anwendungen Des Nanobereichsunclassified
“…Fe 3+ or Mn 2+ can further serve as imaging tracking indicators for diagnosis and treatment. Recent study has shown that the nMOF MIL-100 containing Fe 3+ can induce pyroptosis in cancer cells controlled by the extracellular pH [29]. In parallel, the organic ligands in nMOFs can also play an important role in contributing the therapeutic efficacy or regulating the interaction between the host and guest, thus modulating the drug release.…”
Section: Introductionmentioning
confidence: 99%